Combined action of adsorption and catalytic oxidation in aluminum dye removal by groundwater treatment waste - Sodaitienė, Edita; Kaušpėdienė, Danutė; Gefenienė, Audronė; Ragauskas, Romas; Ramanauskas, Rimantas (Journal of Environmental Engineering and Landscape Management, 2022)
The performance of groundwater treatment waste (GWTW) as an adsorbent and catalyst in the decoloration of aluminum dye Sanodure green LWN (SG) solution was investigated. The raw GWTW was more suitable for dye removal than calcined at 800 °C temperature. The catalytic activity of GWTW in Fenton-like reactions in sunlight increases with decreasing pH from 5.5 to 2.5 and increasing temperature from 20 to 60 °C. The rate of 70% decoloration in the first 5 min and 92% after 50 min of 100 mg/L SG dye solution was reached at 50 °C and pH 3. Kinetics of the SG dye color removal fitted well with the double exponential and two-stage pseudo-first-order kinetic models. The activation energy of the first stage of the SG dye degradation reaction is 30.45 kJ/mol. GWTW could be re-used for the pre-treatment of dye-contaminated wastewater before entering the wastewater treatment plant.